The Long Road to Agreement: Analyzing the Dynamics of the Indonesia-Australia CEPA Negotiation - Safitriyani; Tobing, Fredy Buhama Lumban (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
The signing of the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) in 2019 and its ratification by Indonesia in 2020 marked a significant milestone in the economic relationship between the two nations. IA-CEPA goes beyond mere trade cooperation, encompassing a broader spectrum of economic collaboration across diverse sectors. However, the IA-CEPA negotiation process was challenging, notably a lengthy three-year hiatus from 2013 to 2016. This article delves into the reasons behind Indonesia's decision to persevere with IA-CEPA negotiations despite the extended delay, employing a qualitative methodology with a deductive approach using negotiation theory. The study finds that Indonesia's continued engagement stemmed from recognizing IA-CEPA as a crucial economic deal for expanding market access to Australia and attracting investment into Indonesia. Despite facing domestic political hurdles and shifts then, Indonesia maintained its commitment to the agreement, viewing it as an important step in strengthening the strategic partnership between the two countries.